Konsep Islamisasi Ilmu Pengetahuan Menurut Ismail Raji Al-Faruqi - Ela Komala; Nanat Fatah Natsir; Erni Haryanti (Peneliti.net, 2021)
Educational crises and other problems in the Islamic world have emerged for a long time, these issues are very urgent to be solved, among others, the occurrence of a dichotomy in Islamic education. This happens because of the enormous influence of western science and technology on the views, styles and patterns of people's lives. The purpose of this study is to analyze the concept of the Islamization of science. The research method used is literature study. The results of the study show that Islamization of science means an attempt to redefine knowledge, namely, defining, rearranging data, rethinking arguments and rationalizations regarding the data, reassessing conclusions and interpretations, reshaping goals and doing so in a way that allows the discipline to enrich the vision and struggle. Islam. The Islamization program of al-Faruqi's science consists of 12 work programs and then these work programs are made into 5 objects of the work plan for the Islamization of science.